The Influence of DNA Extraction and Lipid Removal on Human Milk Bacterial Profiles - Anna Ojo-Okunola; Shantelle Claassen-Weitz; Kilaza S. Mwaikono; Sugnet Gardner-Lubbe; Heather J. Zar; Mark P. Nicol; Elloise du Toit (Methods and Protocols, 2020)
Culture-independent molecular techniques have advanced the characterization of environmental and human samples including the human milk (HM) bacteriome. However, extraction of high-quality genomic DNA that is representative of the bacterial population in samples is crucial. Lipids removal from HM prior to DNA extraction is common practice, but this may influence the bacterial population detected. The objective of this study was to compare four commercial DNA extraction kits and lipid removal in relation to HM bacterial profiles. Four commercial DNA extraction kits, QIAamp® DNA Microbiome Kit, ZR Fungal/Bacterial DNA MiniPrep™, QIAsymphony DSP DNA Kit and ZymoBIOMICS™ DNA Miniprep Kit, were assessed using milk collected from ten healthy lactating women. The kits were evaluated based on their ability to extract high quantities of pure DNA from HM and how well they extracted DNA from bacterial communities present in a commercial mock microbial community standard spiked into HM. Finally, the kits were evaluated by assessing their extraction repeatability. Bacterial profiles were assessed using Illumina MiSeq sequencing targeting the V4 region of the 16S rRNA gene. The ZR Fungal/Bacterial DNA MiniPrep™ and ZymoBIOMICS™ DNA Miniprep (Zymo Research Corp., Irvine, CA, USA) kits extracted the highest DNA yields with the best purity. DNA extracted using ZR Fungal/Bacterial DNA MiniPrep™ best represented the bacteria in the mock community spiked into HM. In un-spiked HM samples, DNA extracted using the QIAsymphony DSP DNA kit showed statistically significant differences in taxa prevalence from DNA extracted using ZR Fungal/Bacterial DNA MiniPrep™ and ZymoBIOMICS™ DNA Miniprep kits. The only difference between skim and whole milk is observed in bacterial profiles with differing relative abundances of Enhydrobacter and Acinetobacter. DNA extraction, but not lipids removal, substantially influences bacterial profiles detected in HM samples, emphasizing the need for careful selection of a DNA extraction kit to improve DNA recovery from a range of bacterial taxa.